INCREASING COMMUNITY PARTICIPATION ACTIVITY THROUGH LEARNING MENTORING - Fukrotutsauroh, Aas (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Real Working Lecture (KKN) is one of dedication to the community in which students to apply knowledge and skills they have significantly according to their areas of expertise. Real Work Lecture is a form of manifestation of Tri Dharma College .In learning activities are expected to increase the Participation of society through activities that exist in society. KKN students participating in the Faculty of Education in collaboration with the University of Djuanda Bogor sub district community Susukan Bojonggede Bogor Regency to utilize community resources in implementing the mentoring program belajar. Kuliah Real Work (KKN) conducted by the Faculty of Education University of Djuanda Bogor expected to increase public participation in the activities of tutoring for the creation of an effective and efficient learning.